2019
DOI: 10.1186/s12906-019-2515-7
|View full text |Cite
|
Sign up to set email alerts
|

Combining an in silico approach with an animal experiment to investigate the protective effect of troxerutin for treating acute lung injury

Abstract: Background Troxerutin (TRX), a naturally occurring flavonoid in various fruits, has been reported to exhibit numerous pharmacological and biological activities in vitro and in vivo. However, the molecular mechanisms underlying TRX as a treatment for disease are poorly understood. Methods Using pharmacophore mapping and inverse docking, a set of potential TRX target proteins that have been associated with multiple forms of diseases was obtained. Bioinformatic analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…These effects of troxerutin were comparable with those of 5 mg/kg DEX. Network pharmacology analysis and in vivo experiments showed that troxerutin markedly prevented the MAPK and NF-κB signaling pathway [ 174 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…These effects of troxerutin were comparable with those of 5 mg/kg DEX. Network pharmacology analysis and in vivo experiments showed that troxerutin markedly prevented the MAPK and NF-κB signaling pathway [ 174 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…It is widely reported that TXR is a phytochemical with proven health benefits. It also has very low toxicity (LD 50 of 27160 mg/kg body weight in rats) and is safe for human use ( Zhang et al, 2015a ; Zhang et al, 2015b ; Shan et al, 2018 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that TXR is a phytochemical with proven health benefits. It also has a very low toxicity (LD50 of 27160 mg/kg body weight in rat) and safe for human use (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%